Foundations of Islamic international relations - Shuriye, Abdi Omar (Universiti Sains Islam Malaysia (USIM), 2004)
The current events on the relation between the West and Muslim world dictate comprehension of fundamental features of Islamic international relations. Muslim intellectuals have to contribute to this timely phenomenon in order to enhance the true picture of Islamic view on the subject. This could only be done with the condition that one refers to the views of Muslim classical jurists on the issue and interpret these views according to the time-space factual experience. The typical legalistic format and traditional approach to the study of international relations will no longer be applicable. Muslim-non-Muslim relation is not based on a "state of war" as depicted by minority hatred-oriented Muslim individuals. Historical dimensions on the aforementioned relation are indicative of this assertion. Muslims should not limit themselves on the framework of operational details of early juridical rulings rather should respond to current events on international relations according to the political and social situations of the contemporary world order.